2014
DOI: 10.1515/forum-2013-0146
|View full text |Cite
|
Sign up to set email alerts
|

A twisted Bass–Heller–Swan decomposition for the algebraic K-theory of additive categories

Abstract: We prove a twisted Bass-Heller-Swan decomposition for both the connective and the non-connective -theory spectrum of additive categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The proof of the following result can be found in [19]. The case where the Zaction on B is trivial and one considers only K-groups in dimensions n ≤ 1 has already been treated by Ranicki [23, Chapter 10 and 11].…”
Section: The Twisted Bass-heller-swan Theorem For Additive Categoriesmentioning
confidence: 99%
“…The proof of the following result can be found in [19]. The case where the Zaction on B is trivial and one considers only K-groups in dimensions n ≤ 1 has already been treated by Ranicki [23, Chapter 10 and 11].…”
Section: The Twisted Bass-heller-swan Theorem For Additive Categoriesmentioning
confidence: 99%
“…This is well-known when the coefficient is a ring and has been recently generalized by Lück-Steimle [26, Theorem 0.1, Remark 0.2] to with coefficient in any additive category. Using this sequence and the assumption that the K-theoretic FJC holds for G with coefficient in R, we see that Denote the Nil-groups N K n (O G (E(G ⋊ β Z), R); β) as defined in [26] by N il Because G is torsion free and satisfies the L-theoretic FJC with coefficient in Z, Theorem B applies and the L-theoretic FJC with coefficient in Z holds for G ⋊ Z. Therefore, by a standard surgery long exact sequence argument, we see that the simple Borel conjecture holds for G ⋊ Z.…”
Section: 2mentioning
confidence: 99%
“…In [22,Section 8] it is shown that if A is idempotent complete, then K(χ) is part of a homotopy fiber sequence (6.8)…”
Section: Compatibility With Colimitsmentioning
confidence: 99%
“…It is conceivable that the twisted Bass-Heller-Swan decomposition for connective K-theory, which is described in Theorem 6.1 and whose proof is given in [22], can be extended directly to the non-connective setting described in Theorem 6.2 using Schlichting's non-connective version of K-theory for exact categories and his localization theorem instead of Waldhausen's approximation and fibration theorems.…”
Section: Compatibility With Colimitsmentioning
confidence: 99%
See 1 more Smart Citation